Feasibility of “Tirta Ardana” Sea-Themed Collection: Adapting 18th Century Corsets into Contemporary Bustier - Agniafrisca, Nabila Keysha; Musdalifah, Musdalifah (Journal of Creativity Student, 2026)
Contemporary fashion design is a creative approach that reflects current trends through innovative visual expressions. Currently, contemporary fashion is increasingly exploring the integration of historical fashion elements with visual interpretations of nature. In response to this context, this study aims to reinterpret historical elements in a contemporary context through the development of “Tirta Ardana” fashion, which integrates the voluminous bustier silhouette characteristic of the 18th-century Victorian era with contemporary aesthetics, drawing inspiration from ocean waves. The method used is practice-based research, adapted from the ADDIE (Analysis, Design, Development, Implementation, Evaluation) procedure. Technical innovations focus on the construction of an 8-panel bustier pattern and material optimization to achieve a stable and voluminous hourglass structure without excessive weight. Validation through feasibility testing by fashion experts resulted in an average score of 85.78%, categorizing the product as “Highly Feasible.” These findings confirm that the construction techniques and final quality of the “Tirta Ardana” successfully synergize contemporary aesthetics with functional stability optimally.